Pilot study for deposition of zirconia by plasma CVD - Espinoza-Pérez, Léster; López-Honorato, Eddie (Nexo Revista Científica, 2021)
This work reports on preliminary tests carried-out for the deposition of zirconia coatings on stainless steel substrates using the Plasma-enhanced Chemical Vapor Deposition (PECVD) technique. Deposition of zirconia using this technique allows the control of variables such as deposition temperature, plasma power, operating pressure, amount of precursor available for the formation of species in the gas phase, volumetric flow of carrier and oxidant gases and evaporation temperature of the precursor. A variable that does not operate at its optimum point is enough to avoid obtaining zirconia deposits or obtaining heterogeneous deposits on the surface of the substrate. Preliminary depositions were performed at 500 and 900 °C, varying the plasma power between 100-250 W and the evaporation temperature of the precursor at 80 and 120 °C. Homogeneous films were obtained at 500 °C/250 W/120 °C. However, increasing the evaporation temperature of the precursor from 80-120 ºC to 200 °C improved the deposition efficiency. It was also determined that the optimal position of the substrate is in the centre of the furnace heating zone and that the deposition temperature and the % oxygen in the plasma directly influence the morphology and crystalline structure obtained. These preliminary results were the starting point for evaluating the influence of other variables on the chemical composition, crystalline structure, morphology and thickness of yttria-stabilized zirconia coatings (YSZ).